Shared and Unique Immune Alterations in Pre-clinical Autoimmunity - Slight-Webb, Samantha (Curr Opin Immunol, 2019)
Progression from health to a classified autoimmune disease is an evolving process that can happen rapidly in some diseases, but usually takes years to develop. Specific immune alterations predate pathogenic autoimmunity and can be used as disease biomarkers to identify high-risk individuals for prevention studies applied in the pre-clinical state. Here we discuss recent findings that illuminate specific immune pathways that are altered in the earliest phases of pre-clinical autoimmunity as well as those mediators more closely associated with later clinically apparent and classified disease onset.